Comparison of polyomavirus (BK virus and JC viruses) viruria in renal transplant recipients with and without kidney dysfunction - Taheri, Shahram (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: Post-transplant infection with polyoma viruses (BK and JC viruses) is an important cause of graft loss and nephropathy. The objective of this study was to compare the frequency of BK and JC viruria in renal transplant recipients with and without graft dysfunction. METHODS: In a case-control study, we selected 60 kidney transplant patients with and without graft dysfunction in the first two years after transplantation. Each group consisted of 30 patients evaluated for basic demographic and laboratory characteristics. First morning urine samples were sent for BK and JC virus detection with QIAamp DNA Mini Kit and real-time polymerase PCR. Chi-square test with Yates’ correction, Student t-test and Mann-Whitney U test were used as indicated. P value of less than 0.05 was regarded as statistically significant. RESULTS: Both groups were similar in age, gender, and time after transplant and pretransplant dialysis. In both groups, seven patients (23.3%) were JC virus positive whereas in case group 14 patients (46.7%) and in control group 9 patients (30%) were BK virus positive. There were no statistical significant difference between case and control groups for both JC and BK virus infection rate. CONCLUSIONS: We concluded that JC and BK virus infection is very prevalent in the first 2 years after transplant and might be monitored appropriately.